TENDENCY OF PLAYERS IS TRIAL AND ERROR: CASE STUDY OF COGNITIVE CLASSIFICATION IN THE COGNITIVE SKILL GAMES - Moh. Aries Syufagi; Mauridhi Hery Purnomo; Mochamad Hariadi (Jurnal Ilmu Komputer dan Informasi, 2012)
To assess the cognitive level of player ability is difficult; many instruments are potentially biased, unreliable, and invalid test. Whereas, in serious game is important to know the cognitive level. If the cognitive level can be measured well, the mastery learning can be achieved. Mastery learning is the core of the learning process in serious game. To classify the cognitive level of players, researchers propose a Cognitive Skill Game (CSG). CSG improves this cognitive concept to monitor how players interact with the game. This game employs Learning Vector Quantization (LVQ) for optimizing the cognitive skill input classification of the player. Training data in LVQ use data observation from the teacher. Populations of cognitive skill classification in this research are pupils when playing the game. Mostly players cognitive skill game have cognitive skill category are Trial and Error. Some of them have Expert category, and a few included in the group carefully. Thus, the general level of skill of the player is still low. Untuk menilai tingkat kognitif dari kemampuan pemain sangatlah sulit; banyak instrumen yang berpotensi bias, tidak dapat diandalkan, dan merupakan tes yang tidak valid. Padahal, dalam serious game penting untuk mengetahui tingkat kognitif. Jika tingkat kognitif dapat diukur dengan baik, penguasaan pembelajaran dapat dicapai. Penguasaan belajar adalah inti dari proses belajar dalam serious game. Untuk mengklasifikasikan tingkat kognitif pemain, kami mengusulkan Cognitive Skill Game (CSG). CSG meningkatkan konsep kognitif untuk memantau bagaimana pemain berinteraksi dengan permainan. Permainan ini menggunakan Learning Vector Quantization (LVQ) untuk mengoptimalkan input klasifikasi keterampilan kognitif pemain. Data trining dalam observasi LVQ menggunakan data dari guru. Populasi klasifikasi keterampilan kognitif dalam penelitian ini adalah siswa saat memainkan permainan. Sebagian besar pemain CSG berkategori keterampilan kognitif adalah coba-coba. Beberapa dari mereka memiliki kategori Ahli, dan sedikit yang termasuk dalam kelompok hati-hati. Dengan demikian, secara umum kemampuan pemain masih rendah.